Historiografía académica y historiografía militante en Argentina y Uruguay - DEVOTO, Fernando (BIBLOS, 2004)
ACHA, OMAR; BORUCKI,ALEX; HOURCADE,EDUARDO; LESGART,CECILIA N.; REALI,LAURA; ROBILOTTI,CECICLIA; RODRIGUEZ,MARTHA; STORTINI,JULIO; ZUBILLAGA,CARLOS